2019
DOI: 10.1039/c9ra03362a
|View full text |Cite
|
Sign up to set email alerts
|

Excellent microwave absorption properties based on a composite of one dimensional Mo2C@C nanorods and a PVDF matrix

Abstract: A Mo2C@C/PVDF composite with excellent absorption performance has been synthesized. The results indicate that the maximum reflection loss can reach −39.0 dB, and the absorbing bandwidth is up to 3.1 GHz at a thickness of 2.0 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…It reduced the reflection of electromagnetic waves on the surface of the material, thus most electromagnetic waves were attenuated inside the material. The comparison of wave absorption performance of as-prepared ZnFe 2 O 4 @SiO 2 @RGO/PVDF samples with similar composites is presented in Table . The ZnFe 2 O 4 @SiO 2 @RGO/PVDF shows superiority in both optimal RL value and thickness. Therefore, it will be suitable for wave absorption applications.…”
Section: Resultsmentioning
confidence: 99%
“…It reduced the reflection of electromagnetic waves on the surface of the material, thus most electromagnetic waves were attenuated inside the material. The comparison of wave absorption performance of as-prepared ZnFe 2 O 4 @SiO 2 @RGO/PVDF samples with similar composites is presented in Table . The ZnFe 2 O 4 @SiO 2 @RGO/PVDF shows superiority in both optimal RL value and thickness. Therefore, it will be suitable for wave absorption applications.…”
Section: Resultsmentioning
confidence: 99%
“…d) And optimal EAB versus filler loading of various 1D absorbers. [47][48][49][50][51][52][53] matching and quarter-wavelength thickness, allowing most of the EM wave to enter and cancel, strong attenuation ability is a key for good absorbing performance. The performances of the typical absorbers are summarized and shown in Figure 6d and Table S1 (Supporting Information).…”
Section: Em Parameters and Em Wave Absorption Propertiesmentioning
confidence: 99%
“…Figure 6. a) The calculated RL at different thicknesses, b) the EAB versus thicknesses the corresponding frequency,and c) impedance matching degree with (1/4)λ curve for the Mo-SiC/C-1100/paraffin, respectively. d) And optimal EAB versus filler loading of various 1D absorbers [47][48][49][50][51][52][53]. …”
mentioning
confidence: 99%
“…It is well known that either SiC or Ti 3 C 2 has very large particle size even up to several microns, which means that these carbides particles cannot fully contact with carbon matrix, and thus, the contribution from interfacial polarization may be insufficient in such carbon/carbide composites [29,32]. More recently, some attempts were made to decorate carbon matrix with some unconventional carbide particles, whose ultrafine particle size could generate good dispersion and abundant interfaces, resulting in a significant enhancement in microwave absorption [33][34][35][36][37]. For example, Dai et al pioneered the involvement of Mo 2 C nanoparticles in carbon matrix through the pyrolysis of Cu-Mo-based metal organic frameworks (MOFs) and the subsequent removal of Cu species, and they confirmed that the synergistic effect of carbon frameworks and Mo 2 C nanoparticles were responsible for the good reflection loss (RL) characteristics [34].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Dai et al pioneered the involvement of Mo 2 C nanoparticles in carbon matrix through the pyrolysis of Cu-Mo-based metal organic frameworks (MOFs) and the subsequent removal of Cu species, and they confirmed that the synergistic effect of carbon frameworks and Mo 2 C nanoparticles were responsible for the good reflection loss (RL) characteristics [ 34 ]. Li et al conducted the coating of carbonaceous layer on pre-prepared MoO 3 nanowires through hydrothermal carbonization of glucose solution and then transformed this precursor into final Mo 2 C@C nanowires under a high-temperature inert atmosphere, and they demonstrated that the composition and microstructure were favorable for the consumption of EM energy by multiple polarization relaxations [ 35 ]. In our previous work, we also harvested Mo 2 C/C composites from Mo-substituted ZIF-8, whose microwave absorption performance was found to be superior to those counterparts with SiC and Ti 3 C 2 [ 37 ].…”
Section: Introductionmentioning
confidence: 99%